2017
DOI: 10.1021/acs.est.6b06576
|View full text |Cite|
|
Sign up to set email alerts
|

Formation of Low-Molecular-Weight Dissolved Organic Nitrogen in Predenitrification Biological Nutrient Removal Systems and Its Impact on Eutrophication in Coastal Waters

Abstract: To alleviate eutrophication in coastal waters, reducing nitrogen (N) discharge from wastewater treatment plants (WWTPs) by upgrading conventional activated sludge (CAS) to biological nutrient removal (BNR) processes is commonplace. However, despite numerous upgrades and successful reduction of N discharge from WWTPs, eutrophication problems persist. These unexpected observations raise the possibility that some aspects of BNR yield environmental responses as yet overlooked. Here, we report that one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 40 publications
1
56
2
Order By: Relevance
“…First, two additional samples collected near sewage treatment plants upstream at Guangzhou and downstream at Macau showed depleted δ 15 DON values (−2.5‰ and −0.9‰). Second, nitrifying bacteria are known to produce soluble microbial products during the biological processing of domestic sewage, contributing large amounts of newly produced DON to the DON pool in the effluent (Eom et al, ; Ni et al, ), which would therefore add isotopically depleted DON to the estuary. In fact, recent work employing stable and radiogenic isotopic techniques has also shown that the final treated effluents are depleted in δ 13 DOC (−29‰ to −27.9‰) relative to raw sewage (−22.7‰ to −23.6‰), which was attributed to the new sources of OC added during the treatment processes (Bridgeman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, two additional samples collected near sewage treatment plants upstream at Guangzhou and downstream at Macau showed depleted δ 15 DON values (−2.5‰ and −0.9‰). Second, nitrifying bacteria are known to produce soluble microbial products during the biological processing of domestic sewage, contributing large amounts of newly produced DON to the DON pool in the effluent (Eom et al, ; Ni et al, ), which would therefore add isotopically depleted DON to the estuary. In fact, recent work employing stable and radiogenic isotopic techniques has also shown that the final treated effluents are depleted in δ 13 DOC (−29‰ to −27.9‰) relative to raw sewage (−22.7‰ to −23.6‰), which was attributed to the new sources of OC added during the treatment processes (Bridgeman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since dissolved inorganic nitrogen (DIN) can be efficiently removed in wastewater treatment plants (WWTPs), especially those with biological nutrient removal processes, dissolved organic nitrogen (DON) has become a non-negligible even major portion (25–95%) of residual nitrogen in the effluent. In particular, microbe-derived DON (i.e., mDON) constitutes the major portion of effluent DON in the conventional activated sludge (AS) process . These mDON substances, such as amino acids and their derivates, are active precursors of nitrogenous disinfection byproducts .…”
Section: Introductionmentioning
confidence: 99%
“…These mDON substances, such as amino acids and their derivates, are active precursors of nitrogenous disinfection byproducts . More importantly, AS-derived mDON is highly bioavailable to facilitate phytoplankton growth but recalcitrant to degradation by AS-like communities . Hence, developing non-AS-based technologies for mDON control is practically meaningful to alleviate DON contamination, which could further reduce nitrogen discharges and ultimately mitigate eutrophication in aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have investigated the removal of dissolved inorganic nitrogen (DIN) using both processes successfully, but very little attention is paid to the removal of dissolved organic nitrogen (DON). Excessive release of DON into the environment can have negative effects; for example, as a nitrogen‐containing nutrient, DON can facilitate the growth of microorganisms (Eom et al, 2017) and meet the needs of harmful algal species such as Karenia brevis , resulting in an algal bloom (Rabalais, 2002; Sinclair et al, 2009).…”
Section: Introductionmentioning
confidence: 99%